Silent hyperlipidaemia modulated vascular endothelial markers - Marwan Merkhan; Jehan Mohammad; Zainab Fathi; Zaid Younus; Sameer M. Mahmood; Marwa Mohammed (Pensoft Publishers, 2021)
The aetiology of ischemic heart diseases is mainly based on atherosclerosis of coronary artery. Inflammation and oxidative reactions are initiating and aggravating the illness resulting in pathological remodelling of vasculaturze at site of injury. Endothelium lining of blood vessels participated in the reaction biochemically through releasing some proteins into circulatory system which further complicate the condition. The aim of this study was to determine early diagnosed hyperlipidaemia-associated changes of the plasma level of some of these endothelial biomolecules. Compared to healthy control, hyperlipidaemic patients have significantly increased arginase, metalloendopeptidase, peroxidase, myeloperoxidase, and peroxynitrite with concomitant reduction in arylesterase and nitric oxide. The present study concluded that hyperlipidaemia play a great role in modulation of certain plasma protein markers which might be directly related to patient pathological condition or could be used as a tool for diagnosis or patient follow up indicating the stage of vasculature remodelling, healing, inflammation or resolution.